Konsep Hukum Kontrak Terapeutik dan Hubungan Kontraktual Berbasis Gentlemen’s Agreements - Wijaya, Yudi Yasmin (Fakultas Hukum Universitas Islam Indonesia, 2026)
The use of the term therapeutic contract in Indonesia originates from opinions underpinning the Guide to Conduct of the Indonesian Medical Code of Ethics (KODEKI). Based on a contractual relationship, agreements about medical treatment are generally conducted informally and without written document, given the occupied environment of medical services. Nevertheless, in certain cases, contractual issues give rise to legal arguments concerning informed consent. Such problems emerge when routine medical procedures resulted in harm to patients, and the absence of informed consent may generate further liability for medical practitioners and even the hospitals. Against this legal issue, this article examines the extent to which contract law influences the therapeutic contractual relationship, and whether the nature of the therapeutic contract ought properly to be regarded as an informal gentlemen’s agreement or as a legally binding obligation. The study employs doctrinal legal research methods, adopting both statutory and conceptual approaches. The analysis is further supplemented by a minor comparative study, drawing upon Book Seven of the Nieuw Burgerlijk Wetboek (NBW) and Act No. 17 of 2023 of Republic of Indonesia about Health. The findings suggest that the therapeutic contract constitutes a distinct form of contract which should be differentiated from informed consent, by virtue of its trust-based character akin to a gentlemen’s agreement. Through recommendations for an ideal codification, this study aspires to provide a prescriptive foundation for the legal recognition of therapeutic contracts in Indonesia.